Uterine Perforation after Manual Vacuum Aspiration - Joshi, Smrity Mool (Nepal Journal of Obstetrics and Gynaecology, 2019)
Surgical modality of abortion should be backed up by adequate skill and facility in service delivery as well as in detecting and managing complications. Keywords: abortion, hemoperitoneum, manual vacuum aspiration